Edna Pontellier's endeavors as the main character in Kate Chopin’s "The Awakening" in the nineteenth-century liberal feminism - Devi Hellystia (English Education Journal, 2021)
This study analyzed the struggle of Edna Pontellier in the 19th-century liberal feminism in the novel entitled The Awakening written by Kate Chopin. Liberal feminism assumes that the main problem of gender inequality is the domination of institutions by men. Men control the economic sphere, political sphere, along with other things. 19th-century liberal feminism put its focus on women's equal liberty. In general, the novel is about Edna Pontellier, the woman who was trapped in the figure of a mother and wife. She struggled as a woman in the 19th-century to get equal liberty and follow her desires. The researcher used the qualitative method in analyzing the struggle of Edna Pontellier. The results of this study show Edna’s struggles to pursue her desires through Mill and Taylor’s 19th-century liberal feminism theory. She wanted to get the same political rights, economic opportunities, and education that men get. The results also showed the two things that lead Edna to become a figure of liberal feminism: an unhappy married life and her desire to free herself.